DNA methylation‐based biomarkers of aging were slowed down in a two‐year diet and physical activity intervention trial: the DAMA study. Issue 10 (18th September 2021) - Fiorito, Giovanni; Caini, Saverio; Palli, Domenico; Bendinelli, Benedetta; Saieva, Calogero; Ermini, Ilaria; Valentini, Virginia; Assedi, Melania; Rizzolo, Piera; Ambrogetti, Daniela; Ottini, Laura; Masala, Giovanna
Abstract: Several biomarkers of healthy aging have been proposed in recent years, including the epigenetic clocks, based on DNA methylation (DNAm) measures, which are getting increasingly accurate in predicting the individual biological age. The recently developed "next‐generation clock" DNAmGrimAge outperforms "first‐generation clocks" in predicting longevity and the onset of many age‐related pathological conditions and diseases. Additionally, the total number of stochastic epigenetic mutations (SEMs), also known as the epigenetic mutation load (EML), has been proposed as a complementary DNAm‐based biomarker of healthy aging. A fundamental biological property of epigenetic, and in particular DNAm modifications, is the potential reversibility of the effect, raising questions about the possible slowdown of epigenetic aging by modifying one's lifestyle. Here, we investigated whether improved dietary habits and increased physical activity have favorable effects on aging biomarkers in healthy postmenopausal women. The study sample consists of 219 women from the "Diet, Physical Activity, and Mammography" (DAMA) study: a 24‐month randomized factorial intervention trial with DNAm measured twice, at baseline and the end of the trial. Women who participated in the dietary intervention had a significant slowing of the DNAmGrimAge clock, whereas increasing physical activity led to a significant reduction of SEMs in crucial cancer‐related pathways. Our study provides strong evidence of a causal association between lifestyle modification and slowing down of DNAm aging biomarkers. This randomized trial elucidates the causal relationship between lifestyle and healthy aging‐related epigenetic mechanisms. Abstract : In a 24‐month randomized factorial intervention trial, dietary and physical activity interventions slowed down DNA methylation‐based biomarkers of aging.